[OP.7A.08] A POLYMORPHISM IN THE NORADRENALINE TRANSPORTER GENE IS ASSOCIATED WITH INCREASED BLOOD PRESSURE IN PATIENTS WITH RESISTANT HYPERTENSION. (September 2017) - Eikelis, N.; Hering, D.; Marusic, P.; Walton, A.; Lambert, E.; Esler, M.; Schlaich, M.; Lambert, G.
Abstract : Objective: Noradrenaline (NA) released from sympathetic nerves is rapidly inactivated through active transport back into nerve terminals via the action of the noradrenaline transporter (NET). NET impairment is evident in several clinically important conditions including hypertension. We aimed to determine whether a single nucleotide polymorphism (SNP), rs7194256, in the 3' untranslated region of the NET gene, which we previously identified, is associated with blood pressure and indices of noradrenaline kinetics. Design and method: Ninety two consecutive patients with resistant hypertension (RH) have been recruited for the study (59% males, age 61.9 ± 1.3 years, BMI 32.0 ± 0.6 kg/m 2, mean ± SEM). Twenty-four hour ambulatory blood pressure monitoring was assessed using an oscillometric Spacelabs 90207 or 90217 monitors (Spacelabs Medical Inc, Redmond, WA, USA). Genotyping of rs7194256 was performed using a pre-developed TaqMan SNP Genotyping Assay (Thermo Fisher Scientific). Plasma catecholamines were analysed using high performance liquid chromatography. Results: T allele of rs7194256 was present in 36% of this cohort. There were no differences in anthropometric measures between patients carrying a C or T alleles. However, patients carrying a T allele had a significantly higher systolic blood pressure (SBP): 24 hr mean SBP 148 ± 2.6 vs 140 ± 2.4; 24 hr max SBP 189 ± 3.2 vs 179 ± 2.6; Day min SBP 121 ± 3.0 vs 112 ± 2.6; Night mean SBP 141 ± 3.0 vs 131 ± 2.5; Night max SBP 170 ± 3.6 vs 159 ± 3.1 mmHg (p < 0.05 for all). T allele carriers had a significantly higher arterial NA concentration: 573 ± 53 vs 377 ± 35 pg/ml (p = 0.002). In addition, the ratio of the intraneuronal NA metabolite 3, 4-dihydroxyphenylglycol to NA was lower in T allele carriers (3.01 ± 0.4 vs 4.08 ± 0.3 pg/ml; p = 0.024), indicative of impaired NET function. Conclusions: The mechanisms contributing to RH are only incompletely understood. Here we demonstrate that a SNP in the NET gene in patients with RH results in impaired NET function with the consequence of higher SBP mediated via the resulting increase in synaptic NA concentration. Impaired NET function appears as a likely contributor to the pronounced activation of the sympathetic nervous system characteristic of patients with RH and may at least in part explain resistance to conventional pharmacotherapy, as first line antihypertensive drugs are no longer antiadrenergic.